2005
DOI: 10.5194/angeo-23-1821-2005
|View full text |Cite
|
Sign up to set email alerts
|

Combined optical, EISCAT and magnetic observations of the omega bands/Ps6 pulsations and an auroral torch in the late morning hours: a case study

Abstract: Abstract. We present here the results of multi-instrument observations of auroral torch and Ps6 magnetic pulsations, which are assumed to be the magnetic signature of the spatially periodic optical auroras known as omega bands. Data from TV and ASC cameras in Barentsburg and NyÅlesund, EISCAT radars in Longyearbyen and Tromsø, as well as IMAGE network were used in this study. The auroral phenomenon which was considered differed from that previously discussed, as it occurred both in an unusual place (high latit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“… Lühr and Schlegel [1994] described omega bands as “a luminous band from which tongue‐like protrusions extend toward the north” with the bright tongues shaped like a Greek Ω and the dark area separating adjacent tongues shaped like an inverted Ω. In recent research, the term omega band has been used to described all of the above variants on what is assumed to be the same basic auroral structure [ Syrjäsuo and Donovan , 2004; Safargaleev et al , 2005; Vanhamäki et al , 2009].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Lühr and Schlegel [1994] described omega bands as “a luminous band from which tongue‐like protrusions extend toward the north” with the bright tongues shaped like a Greek Ω and the dark area separating adjacent tongues shaped like an inverted Ω. In recent research, the term omega band has been used to described all of the above variants on what is assumed to be the same basic auroral structure [ Syrjäsuo and Donovan , 2004; Safargaleev et al , 2005; Vanhamäki et al , 2009].…”
Section: Introductionmentioning
confidence: 99%
“…For example, whereas Akasofu and Kimball's omega bands were distorted arcs, Lyons and Walterscheid [1985] presented observations of omega bands with a dark, inverted W shape formed by bright torches extending poleward from the auroral oval, and Opgenoorth et al [1994] reported "streets" of multiple omega band structures in which undulations on the poleward boundary gave rise to alternating bright humps and dark bays. Lühr and Schlegel [1994] described omega bands as "a luminous band from which tongue-like protrusions extend toward the north" with the bright tongues shaped like a Greek W and the dark area separating adjacent tongues shaped like an inverted W. In recent research, the term variants on what is assumed to be the same basic auroral structure [Syrjäsuo and Donovan, 2004;Safargaleev et al, 2005;Vanhamäki et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…[3] The close connection between eastward drifting omega bands and Ps6 pulsations with periods of 5-40 min has been nearly established by the efforts of a number of authors [e.g., Saito, 1978;Kawasaki and Rostoker, 1979;Baumjohann, 1979;Gustafsson et al, 1981;André and Baumjohann, 1982;Opgenoorth et al, 1983;Wild et al, 2000;Safargaleev et al, 2005;Vanhamäki et al, 2009]. The major source of magnetic pulsations on the ground is thought to be a "meandering" ionospheric Hall current in the presence of a sequence of east-west oriented pairs of upward and downward field-aligned currents (FACs); the former flows out of the bright tongue of the omega band and the latter flows into the dark hole.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are numerous papers describing aurora modulation by Pc5 pulsations (see, e.g., Xu et al, 1993;Safargaleev et al, 2005;Roldugin and Roldugin, 2008), amplitudes of geomagnetic and auroral luminosity pulsations are controlled by different physical factors. Thus, geomagnetic ULF power at high latitudes is essentially controlled by SW or IMF parameters, while the fluctuations of auroral luminosity are more local and their amplitudes depend on the energy distribution of particles at a particular L shell.…”
Section: Data Processingmentioning
confidence: 99%